Comparison of Buprenorphine Treatment for Opioid Dependence in Three Settings - Miotto, Karen (2012)
Although use of buprenorphine in the treatment of opioid dependence is expected to continue to increase, little is known about the optimal setting for providing the medical and psychosocial care required with buprenorphine pharmacotherapy. OBJECTIVE: This study compared buprenorphine therapy delivered in three distinct treatment settings: an opioid-treatment program (OTP) offering individual counseling; a group counseling program utilizing the manualized Matrix Model (MMM) of cognitive-behavioral treatment; and a private clinic setting mirroring standard medical management for buprenorphine treatment provided specifically at a psychiatrist’s private practice (PCS). METHOD: Participants were inducted on buprenorphine and provided with treatment over a 52-week study duration. All participants were scheduled for weekly treatment visits for the first 6 study weeks, and two sites reduced treatment to monthly visits for dispensing of medication and psychosocial counseling. Outcomes include opioid use, participant retention in treatment, and treatment participation. RESULTS: Participants presenting for treatment at the sites differed only by race/ethnicity, and opioid use did not differ by site. Retention differed by treatment site, with the number of participants who stayed in the study until the end of 20 weeks significantly associated with treatment site. The mean number of minutes spent in each individual counseling session also differed by site. Although no difference in opioid use by treatment site was found, results document a significant association between opioid use and buprenorphine dose. DISCUSSION: These results show some differences by treatment site, although the similarity and relative ease in which the sites were able to recruit participants for treatment with buprenorphine, and minor implementation problems reported suggests the feasibility of treatment with buprenorphine across various treatment settings. CONCLUSION: Similar rates of continued opioid use across study sites and few qualitative reports of problems indicates that treatment with buprenorphine and associated psychosocial counseling are safe and relatively easy to implement in a variety of treatment settings.